Implementasi Sistem Manajemen Asset TI Menggunakan GLPI & FusionInventory Software: Studi Kasus PT. SCN Logistic Group - Suroto, Suroto; Yani, Dodi Putra; Fuad, Ahmad; Adyla, M. Faris; Fitrah , Fitrah (Penerbit Goodwood, 2024)
Purpose: The rapid advancement of technology has led to continuous changes in the IT landscape, making it challenging to maintain an accurate and complete asset inventory. SCN Logistic faces difficulties in tracking the whereabouts of its assets. This study proposes a solution for IT asset management using GLPI software and explores the implementation process. The paper aims to contribute to a deeper understanding of how GLPI software can be used to manage IT assets effectively. Research Methodology: A case study approach was used for this research, focusing on PT. SCN Logistic. Data and documents were collected from various sources. The hardware employed includes a Lenovo ThinkPad L14 with an AMD Ryzen 3 processor, 8 GB RAM, and a 256GB SSD. The software used comprises Linux Ubuntu 23.04, Apache2 web server, MariaDB, PHP, GLPI 9, and Fusion Inventory. Results: The GLPI and FusionInventory software successfully records IT assets, such as computers, automatically and stores them in a database. This outcome achieves the research objectives by providing an efficient IT asset management solution for companies using GLPI software. Limitation: A comparative analysis between IT asset management software was not conducted due to time constraints. Contribution: This study offers several benefits for companies: (1) Reduces security risks and gaps, (2) Improves efficiency and increases productivity, and (3) Minimizes overall costs, particularly in terms of updates and support.